Study rheological behavior of refined rapeseed oil - Stanciu, Ioana (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Extracted from rapeseed oil was subjected to purification and refining process and then characterized in terms of rheological, ie dynamic viscosity dependence study in terms of speed shear constant temperature. The results show that at 400C, 600C, 800C and 900C dynamic viscosities of oil decreases with shear rate. At higher shear rates of 20s-1 shows lower viscosity oil fluctuations, became almost constant.